2021
DOI: 10.1103/physreva.103.042801
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of a 1-MeV proton microbeam guided through a poly(tetrafluoroethylene) macrocapillary

Abstract: We present computer simulations about the spatial and temporal evolution of 1 MeV proton microbeam transmitted through an insulating macrocapillary with the length of 45 mm and with the inner diameter of 800 μm. The axis of the capillary was tilted to 1° relative to the axis of the incident beam, which ensured geometrical non-transparency. The simulation is based on the combination of stochastic (Monte-Carlo) and deterministic methods. It involves 1) random sampling of the initial conditions, according to dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In addition, the whole beam could be deflected vertically with the electrostatic deflectors, which proves, that the beam avoided the charge-exchange with the target and kept its initial 1+ charge state. Our experimental finding was certificated by our recent theoretical works [34].…”
Section: Resultsmentioning
confidence: 61%
“…In addition, the whole beam could be deflected vertically with the electrostatic deflectors, which proves, that the beam avoided the charge-exchange with the target and kept its initial 1+ charge state. Our experimental finding was certificated by our recent theoretical works [34].…”
Section: Resultsmentioning
confidence: 61%
“…The observed reduction in beam size with an increase in V 2 indicates an enhanced self-focusing capability of the capillary at higher voltages. Previous investigations [27,28,30,42,43] have shown that the self-focusing capability and ion beam transport through the capillary are determined by the charge patch distribution (σ) on the inner wall of the capillary and the resulting distribution of equipotential lines. To better understand this process, we performed simulations to obtain the distribution of σ and the equipotential lines, as detailed in section 3.…”
Section: Resultsmentioning
confidence: 99%
“…Since Stolterfoht et al first observed the ion guiding effect in insulating materials in 2002 [1], the guiding capabilities of ion beams through capillaries made of various materials have been explored experimentally worldwide. These materials include polyethylene terephthalate (PET) polymers [25][26][27], poly(tetrafluoroethylene) (PTFE) [28], Al 2 O 3 [29], SiO 2 [6,7,30], mica [31,32], Teflon [33], and polycarbonate [5,34]. Furthermore, investigations on capillary guiding effects have been conducted using not only ions but also electrons [35][36][37][38] and negative ions [39,40] as projectiles.…”
Section: Introductionmentioning
confidence: 99%